(untitled) (Konturen, 2020)
Jocelyn Aksin’s research is based in Turkish-German studies with a focus on transnational memory. She has published on the role of Turkish newspapers in Die Brücke vom Goldenen Horn and Bitteres Wasser by Emine Sevgi Özdamar, and received her Ph. D. from Washington University in St. Louis in 2014 with a dissertation on representations of memory in Turkish-German novels by Zafer Şenocak, Aras Ören, Feridun Zaimoğlu, and Emine Sevgi Özdamar. Jocelyn began studying Turkish as a graduate student in the German program at Washington University, and was awarded a fellowship from the American Research Institute in Turkey for advanced Turkish language study at Boğaziçi University (Bosphorus University). After spending nearly eight years in Istanbul where she completed her dissertation and worked as a language teacher, Jocelyn relocated to Greensboro, N.C. and joined the German Program at UNCG as a lecturer in 2018.